KEPÇE KULAK KIKIRDAĞININ ÖNDEN DİLİMLEME YÖNTEMİYLE DÜZELTİLMESİ - AYDIN, Yağmur; GÜZEL, M. Zeki; YILDIRIM, Alpagan Mustafa (Cerrahpaşa Medical Journal, 2014)
Background.- Prominent ears are frequent in the white population with an incidence of 5 percent. Many surgical techniques can roughly be classified as the cartilageincision techniques versus the sutureplacement techniques have been described to correct prominent ears. The purpose of this article is to demonstrate the details of anterior scoring technique for the correction of prominent ears and compared with other published ones. Design.- A total of 63 prominent ears underwent repair. The age of patients at surgery ranged from 9 to 23 years (mean age, 11.8 years). Of 33 patients, 20 were female and 13 were male. The procedure was bilateral in 30 cases, unilateral 3 cases. All patients were treated with anterior scoring technique alone. All patients were placed into a head bandage for 5 to 7 days and then usually for 3 weeks in a headband. Results.- Average follow-up was performed at 4,2 years. There was no encountered any complication. The patient satisfaction survey found that all patients were either very satisfied or extremely satisfied with the overall appearance of the ears. Symmetry was noted to be good to excellent by all the patients- parents and surgeon.